Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Menguatkan Karakter Semangat Kebangsaan dalam Proses Belajar Mengajar di SMK Mahad Mualimin Alwasliyah UISU Medan - Maharani, Tiara; Tampilen, Tampilen; Adlina, Zuraidah (Medan Resource Center, 2024)
This research aims to find out how Pancasila and Citizenship Education teachers strengthen the character of the national spirit in the learning process in the Pancasila and Citizenship Education subject. According to the Big Indonesian Dictionary (KBBI), the definition of character is character, psychological traits, morals or manners that distinguish a person from another, character. The research method in this research is a qualitative exploratory type. The population in the study was class X TKJ Mahad Mualimin Alwasliyah Vocational School (MMA) Uisu Medan. At the beginning of the research, they entered a class with 35 students and were designated as research samples, then conducted interviews with students, Pancasila and Citizenship Education teachers and school principals about the role of Pancasila and Citizenship Education teachers in strengthening the character of students, so as to obtain the actual results. The role of Pancasila and Citizenship Education teachers in strengthening the character of students' national spirit is very important because in learning Pancasila and Citizenship Education, Pancasila values ??are instilled